Performance of Kerinci Ducks Treated by Cattle Rumen-Fluid Supernatant Addition as Source of Crude Enzyme in Rations - A. Budiansyah; Resmi Resmi; Filawati Filawati; U. Haroen (Faculty of Animal Science, Bogor Agricultural University, 2020)
The objective of this study was to determine the effect of varying levels of cattle rumen fluid obtained from abattoirs as sources of a crude enzyme on growth performances and carcass characteristics of Kerinci ducks fed rations based on local feed ingredients. The research was carried out using 140 one-week-old male Kerinci ducks. The experiment used a randomized block design consisted of 5 treatments, each with 4 replicate groups and was blocked based on body weight, while each cage unit consisted of 7 ducks. The treatments applied were R1= 0 mL RFS/kg ration (control), R2= R1 + 22 mL RFS/kg ration, R3= R1 + 44 mL RFS/kg ration, R4= R1 + 66 mL RFS/kg ration, and R5= R1 + 88 mL RFS/kg ration. The experimental ducks were fed the experimental ration for 7 weeks and fed ad libitum according to the treatment. At the end of the 7th weeks of treatment, two ducks from each cage were slaughtered and utilized for analysis of carcass and digestive organs parameters. The results showed that the addition of RFS up to a level of 88 mL/kg ration had no significant effect (p>0.05) on feed consumption, feed conversion, carcass weight, and digestive-organ weight. Still, it had significant effects on body weight gain and final body weight. The highest body weight gain and final body weight were achieved with the addition of RFS at the level of 88 mL/kg ration. It can be concluded that the addition of cattle rumen-fluid supernatant as a source of crude enzymes at the level of 88 mL/kg ration improved the growth performance of local Kerinci ducks.